Design and analysis of a lightweight composite shipping container made of carbon fiber laminates - Turkay Yildiz (Logistics, 2019)
The literature indicates that a 20% reduction in the weight of empty 40-foot shipping containers would result in 28 billion of fuel savings, along with a 3.6 exajoule reduction in the energy demand over containers' 15-year lifetime. Decreasing the energy demand and thereby greenhouse gas emissions by utilizing lightweight shipping containers has been an unexplored strategy. In this regard, this study investigates the possibility of further reducing the weight of an empty container without compromising the structural integrity, strength, and function of a traditional steel container. This research finds that up to an 80% reduction in weight is possible by producing shipping containers with composite materials. This research presents the new design of a 40-foot container made of carbon fiber laminates. The tare weight of a traditional 40-foot shipping container is around 3750 kg. On the contrary, in this research, the weight of a composite design of the same container is calculated to be around 822 kg. Additional tests with various loads, such as lifting the container and stacking loads onto the composite container, are performed to explore the strength and buckling issues of the design presented in this study. The analyses reveal that the composite shipping container is a highly promising candidate for reducing greenhouse gas emissions, providing fuel savings and thus reducing the operational costs of transportation.
Keywords: 650; carbon fibers; composite materials; logistics; shipping container; supply chain; transportation